A review of the genus Trachelas (Araneae: Corinnidae) from China - Zhang, Feng; Fu, Jian-Ying; Zhu, Ming-Sheng (Zootaxa, 2009)
Six species of the genus Trachelas from China are reviewed, with descriptions of two new species: Trachelas fanjingshan sp. nov. and T. fasciae sp. nov. Drassodes digitusiformis (Hu, 2001) is transferred to Trachelas, as a junior synonym of Trachelas alticolus Hu, 2001. Trachelas acuminus (Zhu et An, 1988), T. japonicus Bösenberg et Strand, 1906 and T. sinensis Chen, Peng et Zhao, 1995 are redescribed and illustrated. A key and a distribution map of Chinese Trachelas are provided.